Case Report: Vasculitis Triggered by SIRT in a Patient With Previously Untreated Cholangiocarcinoma - Stamatiou, Antonia; Jankovic, Jeremy; Szturz, Petr; Fasquelle, Francois; Duran, Rafael; Schaefer, Niklaus; Diciolla, Antonella; Digklia, Antonia (Frontiers in Oncology, 2021)
Arising from the biliary tract, cholangiocarcinoma is a rare and aggressive epithelial cancer. According to the primary site, it can be further classified into intrahepatic, perihilar and distal types. Due to the lack of symptoms early in the disease course, most patients are diagnosed at advanced stages. Being not candidates for curative surgical management, these patients are treated with palliative systemic chemotherapy, and their prognosis remains poor. Using radioisotopes like yttrium-90 -labeled microspheres (90Y), radioembolization represents a local approach to treat primary and secondary liver tumors. In the case of intrahepatic cholangiocarcinoma, radioembolization can be used as a primary treatment, as an adjunct to chemotherapy or after failing chemotherapy. An 88-year-old man underwent radioembolization for a previously untreated stage II intrahepatic cholangiocarcinoma. One week later, he presented to our clinic with a non-pruritic maculopapular rash of the lower extremities and abdomen, worsening fatigue and low-grade fever. Laboratory exams, including hepatitis screening, were within normal limits. Showing positive immunofluorescence staining for immunoglobulin M (IgM) and complement 3 (C3) in vessel walls without IgA involvement, the skin biopsy results were compatible with leukocytoclastic vasculitis. Apart from the anticancer intervention, there have been no recent medication changes which could explain this complication. Notably, we did not observe any side effects during or after the perfusion scan with technetium-99m macroaggregated albumin (MAA) performed prior to radioembolization. The symptoms resolved quickly after a short course of colchicine and did not reappear at cholangiocarcinoma progression. In the absence of other evident causes, we conclude that the onset of leukocytoclastic vasculitis in our patient was directly linked to the administration of yttrium-90 -labeled microspheres. Our report therefore demonstrates that this condition can be a rare but manageable complication of 90Y liver radioembolization.